Animal model for sporadic dementia of Alzheimer’s type (SDAT) using streptozotocin and lipopolysaccharide combinations in rats - Rahadian Yudo Hartantyo; Mohammad Rizky Mochtar Hidayat; Abdul Basith Azzam; mulyati mulyati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Sporadic dementia of Alzheimer’s type (SDAT) pathogenesis has not been revealed completely due to the difficulty in creating an appropriate animal model. The purpose of this study was to investigate the effect of single-dose intraperitoneal (IP) induction of streptozotocin (STZ) and lipopolysaccharide (LPS) on the β-amyloid levels and the brain function of experimental rats. Eighteen rats were divided into three groups i.e. control, TRE1 (STZ 60 mg.kg-1 BW + LPS 3 mg.kg-1 BW), and TRE2 (STZ 30 mg.kg-1 BW + LPS 1.5 mg.kg-1 BW). The substances were administered in a single dose. Behavioral tests were started at day-30 after injection, we performed Morris water maze (MWM) and novel object recognition (NOR) tests. Afterward, we measured whole brain and serum β-amyloid levels, as one of the biomarkers of Alzheimer’s Disease (AD), using the ELISA method. In MWM tests, the escape latency and time spent in the target quadrant of treatment groups were significantly higher than those in control at the day-5 MWM test and probe trial. The rats in treatment groups have negative discrimination indexes in NOR tasks, indicating that the rats could not remember the familiar object. Intraperitoneal STZ and LPS significantly increase soluble brain β-amyloid levels of treatment groups than those in the control group. In conclusion, the treatment of STZ (60 mg.kg-1 BW) and LPS (3 mg.kg-1 BW) indicated spatial and recognition memory impairment, along with an increase of brain soluble β-amyloid level in rats.